Towards efficient utilization of nitrogen based fertilizers - Ahmad, Osumanu Haruna; Nik Majid, Nik Muhamad (Universiti Putra Malaysia Press, 2014)
This book explains some of the sustainable ways of utilizing readily available resources such as humic acids, acid sulphates, and zeolites to improve nitrogen use efficiency. The chapters cover aspects of nitrogen dynamics, use of humic acids and acid sulphate soils to improve nitrogen use efficiency, overview on zeolites, mitigation of ammonia volatilization from nitrogenous fertilizers through the use of clinoptilolite zeolite, and fortifying nitrogen based compound fertilizers with clinoptilolite zeolite to improve nutrient use efficiency by plants.